Locked Scapholunate Instability Presenting as a Progressive Injury - Amarasooriya, Melanie; Peramuna, Seneeth; Bain, Gregory (Journal of Wrist Surgery, 2025)
Locked scapholunate instability is described as scapholunate instability occurring with a dislocated proximal pole of the scaphoid. Scapholunate instability is an early stage of perilunate instability. While being rare, complete or proximal pole scaphoid dislocations usually occur as an acute injury and often missed.We present a case of locked scapholunate instability where the proximal pole dislocation developed over a period of 6 weeks following injury. In addition, the membranous part of the scapholunate interosseous ligament was avulsed and interposed between the scaphoid and the lunate, blocking the scaphoid reduction.Multiple ligaments such as the scapholunate interosseous ligament, dorsal intercarpal ligament, and scaphocapitate ligament are likely to be injured in these cases for scaphoid proximal pole to dislocated dorsally, essentially creating a periscaphoid “instability.” Radial-sided “locked periscaphoid” instability, being an intermediate stage between scapholunate instability and perilunate instability, can either progress to perilunate instability or scaphoid dislocation.It is important to follow these patients up for progressive worsening of symptoms and identifying factors that would hinder reduction.
Keywords: scapholunate instability; locked scapholunate instability; carpal instability; scaphoid dislocation